THE EFFECT OF LONG SOAKING OF SEEDS IN KNO3 SOLUTION AND VARIATIONS IN PLANTING MEDIA ON THE GERMINATION OF CIPLUKAN (Physalis angulata L.) SEEDS IN VITRO - hartati, Puji; Hastuti, Endah Dwi; Setiari, Nintya; Nurchayati, Yulita (Jurnal Bioteknologi & Biosains Indonesia (JBBI), 2024)
The Physalis angulata L. (ciplukan), originating from the Solanaceae family, contains secondary metabolites that can be used as medicinal materials. The provision of Physalis angulata seeds is hindered by seed dormancy. Dormancy can be broken by employing a 0.2% w/v KNO3 solution with a specific soaking period. This study aims to optimise the duration of the soaking period for Physalis angulata seed germination and the in vitro growing medium. The seeds were soaked in a 0.2% w/v KNO3 solution for 6 hours, 12 hours, and 24 hours. The soaked seeds were planted in sterile tissue media moistened with Murashige and Skoog (MS) medium solution, a 0.2% w/v KNO3 solution, and distilled water. Generally, the dormancy of Physalis angulata seeds can be broken by soaking them in a 0.2% w/v KNO3 solution. The results of this study indicated that Physalis angulata seeds soaked in a 0.2% w/v KNO3 solution for 6 hours and 12 hours, then planted in sterile tissue media moistened with the MS medium solution, exhibited an optimal germination response.